PERSEPSI DAN KEPATUHAN PEDAGANG KAKI LIMA TERHADAP PERATURAN DAERAH TENTANG KETERTIBAN UMUM DI KOTA BANDUNG - Caturi, Putri Indah; Munawar, Hendrik Sudria; Mufthi, Eky Muhammad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study is motivated by the issue of street vendors’ (PKL) compliance with the Local Regulation (Perda) on Public Order in Bandung City, which often creates tension between the local government and the community. The research aims to analyze street vendors’ perceptions of the regulation, their compliance levels, and the factors influencing the relationship between the two. A mixed-method approach was applied, combining quantitative data from a 3-point Likert questionnaire distributed to 40 street vendors located in Alun-Alun Bandung, Jalan Pasteur, Cicadas, and Tegalega, with qualitative data obtained from in-depth interviews. The results indicate that the majority of street vendors hold negative perceptions of the regulation, particularly regarding fairness and its impact on their income. Quantitative findings reveal that only 25% of respondents show positive perceptions, while 75% remain negative. Compliance levels are also low: only 30% of respondents adequately follow zoning and cleanliness rules, while most often violate operating hours and stall placement. Qualitative findings further highlight that the manner of enforcement by officers and lack of effective socialization contribute to this low compliance. The study concludes that negative perceptions are directly related to lower compliance with the regulation. Therefore, it is recommended that the local government adopt a more humanistic and participatory approach, enhance regulation socialization, provide alternative business spaces, train enforcement officers in persuasive communication, and involve street vendors in the policy-making process.